Factors Affecting the Implementation of Authentic Assessment to Measure Students’ Reading Comprehension: A Case of English Teachers at State Senior High School 1 Purwodadi - Fitria Wahyu Nugraheni; Mursid Saleh; Rudi Hartono (Universitas Negeri Semarang, 2022)
The term of assessment refers to the wide variety of methods or tools that educators use to evaluate or measure students’ learning progress, skill, or acquisition. The benefit of assessment for teachers can be used to gather information on planning and modifying teaching and learning programs for students. This study concerns to the factors affecting the implementation of authentic assessment in reading comprehension. This study was aimed at answering four research questions regarding (1) the implementation of authentic assessment to measure students’ reading comprehension, (2) the correlation between teacher’s background and the implementation of authentic assessment, (3) the correlation between teacher’s professional development and the implementation of authentic assessment, and (4) the correlation between teacher’s belief and the implementation of authentic assessment. The researcher applied quantitative correlation research design. The correlation research design was used since it was appropriate to measure the significant correlation between those two variables. The findings revealed that three teachers as the subject of this research had good effort in implementing authentic assessment. They created various assessment to assess students’ reading comprehension. Based on the observation which has scored, their implementation belongs to good, enough, and fair criteria. The next finding is that based on the SPSS computation, among three factors stated previously, the teacher’s belief is significant correlate to the implementation of authentic assessment, meanwhile teacher’s background and teacher’s professional development are not significant correlate.